Regional variation in U.S dementia trends from 2000-2012 - Jennifer A. Ailshire; Katrina M. Walsemann; Calley E. Fisk (Elsevier, 2022)
Although recent studies report a decline in dementia prevalence among U.S. older adults, national trends may mask subnational variation, particularly given large health and social inequalities linked to geography. To address this gap, we determined if there was subnational variation in reported national dementia trends and if region-specific trends were explained by sociodemographic and health characteristics. Data come from the 2000 (n = 10,447) and 2012 (10,426) waves of the Health and Retirement Study. We used validated methods for dementia classification using proxy and self-respondents. Logistic regression models, adjusted for within-person clustering over time, estimated trends in dementia prevalence by region and census division. We found subnational variation in dementia prevalence in both 2000 and 2012, as well as in change in dementia prevalence during this period. In 2000, dementia prevalence was lowest in the West (8.6%), higher in the Midwest (10.0%) and Northeast (11.1%), and highest in the South (14.6%). Dementia prevalence declined over time across all regions of the U.S. from 2000 to 2012 but remained highest in the South (10.7%) compared to the other regions (7.0-7.8%). Despite downward trends in dementia across the U.S., the prevalence of dementia in the South in 2012 approximated levels found in other regions in 2000. There was relatively less change over time in the West compared to other regions, but dementia prevalence was already quite low in the West in 2000. Within region, trends in dementia prevalence between 2000 and 2012 also varied slightly across census divisions. Subnational variation in changes in dementia prevalence were largely explained by education and health status. Variation in baseline prevalence, as well as differential rates of change, highlight the importance of examining subnational variation in dementia trends.